Pengaruh Penerapan PROLANIS Pada Pasien Diabetes Mellitus Tipe 2 Di Puskesmas Kota Bekasi - Lia Warti; Dian Ratih Laksmitawati; Prih Sarnianto (Fakultas Farmasi Universitas Setia Budi, 2022)
Prolanis is Chronic Disease Management Program; where this program is an integrated health service program and involves other parties such as BPJS, health facilities and patients. Clinical outcomes ultimately impact the quality of life and, in general, if the quality of life grows well, which is indicated by controlled glucose levels. The result of this research is to know the impact of applying Prolanis to measure the quality of life in type 2 Diabetes Mellitus patients at Pekayon Jaya Health Center and Pengasinan Health Center. The method used in this research is a cohort study with data analysis of SPSS version 24. The study was conducted on 80 patients consisting of 40 prolanis patients at Pekayon Jaya Health Center and 40 non-prolanis patients at Pengasinan Health Center within a period of 3 (three) months. Data on the level of knowledge and compliance were collected using a questionnaire. GDP data was taken from monthly patient control visits, and quality of life data was taken using the European Quality of Life-5 Dimension-5 Level (EQ-5D-5L) instrument and the conversion of health utility to the Indonesian value set. The result is there is a significant effect of applying prolanis program in prolanis and non-prolanis patients on the level of knowledge, compliance, and GDP in describing the quality of life. The utility value of prolanis patients was 0.945±0.101 higher than non-prolanis patients, 0.769±0.197. Based on the level of knowledge of prolanis and non-prolanis patients (34.35±2.13: 28.47±4.09), prolanis and non-prolanis patient compliance (6.38±1.66: 5.11±1.45), and fasting blood sugar values ​​of prolanis and non-prolanis patients (110.05±20.67 : 144.20±29.10). The application of Prolanis is said to have a considerable influence on the level of discipline, knowledge, and GDP to the quality of life of patients, both prolanis and non-prolanis.